Tissue Transglutaminase 2 (TGII), Its Protein Expression and Possible Role in Cytoskeletal Regulation during Pregnancy with Applications to Preterm Birth - Thompson, Nicolette (2009)
Background: Preterm labour is linked to higher mortality and morbidity rates. It has many possible causes; however the vast majority are idiopathic. Current pharmacological interventions are ineffective in reducing preterm birth rates and the associated mortality and morbidity. In order to progress, research into the biological and molecular processes occurring in pregnancy and labour has been highlighted. Tissue transglutaminase 2 (TGII) inhibition inhibits contractions, leading onto questions about this multifunction protein’s role in pregnancy and labour